Transient Pseudohypoaldosteronism due to Urinary Tract Infection in Infancy: A Report of 4 Cases. (3rd May 2009) - Nandagopal, Radha; Vaidyanathan, Priya; Kaplowitz, Paul
Abstract : Hyponatremia with hyperkalemia in infancy is an uncommon but life-threatening occurrence. In the first weeks of life, this scenario is often associated with aldosterone deficiency due to salt-wasting congenital adrenal hyperplasia. However, alternative diagnoses involving inadequate mineralocorticoid secretion or action must be considered, particularly for infants one month of age or older. We report four infants who presented with profound hyponatremia accompanied by urinary tract infection, ultimately leading to the diagnosis of transient pseudohypoaldosteronism. Our cases provide support for the idea that the renal tubular resistance to aldosterone is due to urinary tract infection itself rather than to underlying urinary tract anomalies typically found in these infants. Awareness of this condition is important so that serum aldosterone, urine sodium, and urine cultures may be obtained immediately in any infant presenting with hyponatremia and hyperkalemia in whom a diagnosis of congenital adrenal hyperplasia was not found. Adequate replacement with intravenous saline and antibiotic therapy is sufficient to correct sodium levels over 24–48 hours.